2014 IEEE 6th Conference on Engineering Education (ICEED) 2014
DOI: 10.1109/iceed.2014.7194682
|View full text |Cite
|
Sign up to set email alerts
|

The influences of Flipped Classroom: A meta analysis

Abstract: The latest learning methods of 21st century emphasizes on student-centered learning and the use of technology in teaching. Flipped Classroom is one of the latest pedagogies that give attention to active learning through the use of technology as an intermediary in learning and teaching. In contrast to the traditional method where the teacher use 'chalk and talk', Flipped Classroom emphasizes on learning through the student's own knowledge construction. Thus, there are two-way interactions which are among the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 11 publications
0
14
0
1
Order By: Relevance
“…In this study, 21 studies using flipped learning model were analyzed and it was concluded that student achievement was increased by flipped learning in majority of the studies. Another study was conducted by Rahman, Aris, Mohamed and Zaid (2014). In this study, 17 studies on flipped learning model were included in the meta-analysis and it was determined that flipped learning model has a positive effect on student achievement.…”
Section: Flipped Learning Modelmentioning
confidence: 99%
“…In this study, 21 studies using flipped learning model were analyzed and it was concluded that student achievement was increased by flipped learning in majority of the studies. Another study was conducted by Rahman, Aris, Mohamed and Zaid (2014). In this study, 17 studies on flipped learning model were included in the meta-analysis and it was determined that flipped learning model has a positive effect on student achievement.…”
Section: Flipped Learning Modelmentioning
confidence: 99%
“…In Asia, in the past decade, there has been a wave of implementations of the flipped classroom in K‐12 education. When adopting this approach, teachers are confronted with challenges including preparation of instructional videos that provide effective learning guidance (Lai & Hwang, ; Rahman, Aris, Mohamed, & Zaid, ). This implies that more attention has been paid to the development of micro‐lesson videos rather than to developing effective strategies for improving students’ knowledge construction and knowledge internalization (Blau & Shamir‐Inbal, ; Kim, Kim, Khera, & Getman, ).…”
Section: Introductionmentioning
confidence: 99%
“…Few studies conclude that FC does not improve student performance compared to traditional teaching concepts [12,13] while the majority of studies describe positive effects of the FC on student motivation, satisfaction, and performance [8,14,15]. Also, commitment, problem-solving skills, and conceptual understanding can be increased [8].…”
Section: Flipped Classroom and Learning Analyticsmentioning
confidence: 99%